Critical success factors in Chinese cross-border mergers and acquisitions: A study of two Chinese cases in Germany. Issue 4 (5th November 2018) - Chen, Yu; Werle, Herbert; Moser, Roger
Abstract : Purpose: This paper aims to explore the critical success factors (CSFs) in Chinese cross-border Mergers and Acquisitions (M&As) to improve the odds of Chinese overseas acquisition success. Design/methodology/approach: For the multidisciplinary analysis purpose, a SCOPE model is developed to integrate the five key dimensions of Strategic (S), Cultural (C), Organizational (O), Process (P) and External (E) CSFs. Because of the exploratory nature of the research, a case study approach has been applied. Findings: Based on the two in-depth case studies of Lenovo's acquisition of Medion and Sany's acquisition of Putzmeister in Germany, eight CSFs along the five key dimensions have been identified. Apart from the identified CSFs, the two other factors of robust due diligence and M&A project organizational structure fit are worthy of noting. Research limitations/implications: The first limitation relates to the weaknesses of case study research method. The findings derived from the two selected M&A cases cannot be generalized to all the contexts of Chinese cross-border M&As. The second limitation relates to the subjective nature of judgments made by the participants in our empirical study. The identified CSFs were based on the perceptions of the interviewed managers. Practical implications: The research is of high practical importance for Chinese companies doing or considering cross-border M&As. The CSFs identified in this research can direct managerial priorities toward those few areas which should receive careful attention and control to achieve the M&A success. Originality/value: No much empirical research has addressed Chinese cross-border M&As from a CSF perspective. This research helps to fill this research gap and provides new insights for the Chinese companies to increase the success rate in their cross-border M&A projects.